Cognitive control and the non-conscious regulation of health behavior - Rebar, A.; Loftus, Andrea; Hagger, Martin (Frontiers Research Foundation, 2015)
A commentary on 'Cognitive control in the self-regulation of physical activity and sedentary behavior' by Buckley, J., Cohen, J. D., Kramer, A. F., McAuley, E., and Mullen, S. P. (2014). Front. Hum. Neurosci. 8:747. doi: 10.3389/fnhum.2014.00747